MAKNA DAN FUNGSI PANTUN PALANG PINTU DALAM ACARA PERNIKAHAN ADAT MELAYU DI KECAMATAN AIR PUTIH KABUPATEN BATU BARA - Farihatul Hasanah; Juni Ahyar; Maulidawati (Global Action and Education for Society, 2026)
This study aims to describe the meaning and function of the palang pintun pantun in the wedding customs of the Air Putih District community taken from 2 villages and two weddings, namely, Pematang Panjang Village and Gelembis Village. The research method used is descriptive qualitative. Data collection techniques in this study are observation, interviews, documentation, recording, listening and taking notes. The data in this study are pantun sung by poets from both sides of the bride and groom during the wedding reception taking place in Air Putih District, Batu Bara Regency. The data sources in this study are poets who throw pantun and have knowledge of the tradition and the host. Based on the results of the study, 54 data were found. Cultural meanings are 17 data, joke meanings are 12 data, the meaning of inviting thinking is 8 data, the expression of feelings of the heart is 5 data, the meaning of entertaining is 4 data, the meaning of teaching is 2 data, the meaning of advice is 1 data, the meaning of religion or religion is 1 data, with cultural meanings and joke meanings as the most frequently appearing meanings. The function of pantun in the tradition of the palang pintu pantun tradition was found to be 54 data. The language intelligence function has 21 data, the appreciation and gratitude function has 15 data, the affection and love function has 8 data, the education function has 7 data, with the language intelligence and gratitude function appearing most frequently.